Multilocus approach reveals distinct evolutionary units of the South American apapa Pellona flavipinnis (Valenciennes, 1837) (Clupeiformes, Pristigasteridae) - Ximenes, Aline Mourão (Journal of Fish Biology, 2023)
The discovery and characterization of cryptic diversity is important for conservation and management, especially for ichthyofauna, whose diversity is underestimated and understudied. Cryptic diversity is especially common in widely distributed species, and Pellona flavipinnis is one such species. Thus, the aim of the present study was to investigate and test whether P. flavipinnis harbours cryptic diversity. In this study we used the COI and control region sequences and microsatellite loci of 86–114 specimens from 11–12 locations throughout the Amazon basin, depending on the molecular marker used. We also included two COI GenBank sequences from the type locality of the species, the Paraná River. The results from COI sequences showed that P. flavipinnis from the Amazon basin presented two spatially structured lineages differentiated from P. flavipinnis from the Paraná River by 10.6%–9.8% (depending on the lineages) and 45 mutational steps. The genetic distance between the Amazon lineages was 2.4% using COI, with high population differentiation values (ФST = 0.8686 and ФST = 0.8483 for COI and control region, respectively). Among the five species delimitation methods employed, three indicated two lineages in P. flavipinnis in the Amazon basin, and all five methods indicated that the Amazonian lineages are different from that of Paraná. Results from microsatellite loci also showed that P. flavipinnis from the Amazon basin is composed of two evolutionary units. The results of 13 morphometric measurements indicated that there are no differences in shape between the P. flavipinnis lineages in the Amazon basin. The present findings suggest that there are two sympatric lineages of P. flavipinnis in the Amazon basin. © 2023 Fisheries Society of the British Isles.
Keywords: Amazon basin; Bácia Amazonica; Cryptic diversity; Microsatellites; Paraná-Paraguai River; MtDNA; Yellowfin river Pellona